Enhancing human ACE2 expression in mouse models to improve COVID‐19 research - Sun Jiaoyang; Cheng Shaofei; Hong Guangliang; Quan Xiongzhi; Lin Haofeng; Mao Rui; Johannes Grillari; Shi Zheng‐Li; Chen Jiekai; Liu Meiqin; Wu Haoyu; Wu Guangming (FEBS Open Bio)
Mice are one of the most common biological models for laboratory use. However, wild‐type mice are not susceptible to COVID‐19 infection due to the low affinity of mouse ACE2, the entry protein for SARS‐CoV‐2. Although mice with human ACE2 (hACE2) driven by Ace2 promoter reflect its tissue specificity, these animals exhibit low ACE2 expression, potentially limiting their fidelity in mimicking COVID‐19 manifestations and their utility in viral studies. Here, we created and compared hACE2 mouse models generated with different strategies. Our findings show that distinct β‐globin insertion within hACE2 cassette significantly influences its expression, with downstream placement enhancing transcription. Moreover, optimizing hACE2 codons (opt‐hACE2) improves translation efficiency in multiple tissues. Notably, opt‐hACE2 mice displayed more active immune responses and severe COVID‐19 phenotypes following SARS‐CoV‐2 challenge compared to other models. Our study demonstrates the dual regulatory role of β‐globin element in transgene transcription and suggests that opt‐hACE2 mice might serve as valuable tools for SARS‐CoV‐2 research.